Lidocaine, Verapamil 및 Lidocaine-Verapamil 혼합 사용이 기관내 튜브 발관시 혈압과 심박수에 미치는 영향 - 강화자; Wha Ja Kang; 이병익; Byung Ik Rhee; 이봉재; Bong Jae Lee; 김건식; Keon Sik Kim; 신옥영; Ok Young Shin; 신광일; Kwang Il Shin (Korean journal of anesthesiology, 1999)
Background : Tracheal extubation, as well as intubation, causes hypertension and tachycardia. The aim of this study was to compare the effect of verapamil, lidocaine to lidocaine-verapamil combination in attenuating the cardiovascular changes following tracheal extubation and emergence from anesthesia. Methods : Eighty patients (ASA physical status 1) were randomly assigned to one of four groups (n=20 each) ; saline (control), 1 mg/kg lidocaine, 0.05 mg/kg verapamil and lidocaine-verapamil combination. These medication were given intravenously 2 min before tracheal extubation. Changes in blood pressure and heart rate were measured following tracheal extubation. Results : Lidocaine, verapamil and their combination all attenuated the changes of heart rate and blood pressure. The inhibitory effect on changes of heart rate and blood pressure were miximum in group of the combination of lidocaine and verapamil. Conclusion : We conclude that the verapamil 0.05 mg/kg and lidocaine 1 mg/kg given iv concomitantly 2 min before tracheal extubation is a more effective prophylaxis than verapamil or lidocaine for attenuating the cardiovascular changes associated with tracheal extubation. (Korean J Anesthesiol 1999; 36: 250∼255)